Patrimonio geológico - Martinez, Omar Raúl (2008)
Little development has research in Geological Sciences, in our country and particularly in the province of Buenos Aires, had in connection with the sites which require special preservation and protection. However, there are many sites named by geological bibliography which should be valued and preserved as Geological Heritage. The Geological Heritage is just one more element of the natural heritage, and is a big part of our natural inheritance. At the 1972 UNESCO Conference in Paris on the protection of the world cultural and natural heritage, some countries began doing research to get to know, protect and value geological sites, which is undoubtedly a significant resource as well as a key tool for the tourist development of a territory. Making inventories, filing all the information necessary for description, and collecting data of interest so as to keep the inventories updated, all become indispensable to have a thorough knowledge of the geological wealth of an area. The files' designs bear some problems, in some cases, in connection with being too subjective and synthetic, and, in others, too detailed and rigorous.